2014
DOI: 10.3109/08820139.2013.879594
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of costimulatory molecules (CTLA4, ICOS, PD.1 and CD28) and allogeneic hematopoietic stem cell transplantation in Iranian patients

Abstract: Costimulatory molecules are important factors determining the outcome of bone marrow transplant. Because the host ability in costimulatory molecule function may be affected by gene polymorphisms, the aim of the present study was to investigate the effect of CTLA4, ICOS, PD.1 and CD28 gene polymorphisms in outcome of bone marrow transplant patients. A total of 72 recipients were included in this study. CTLA4 (-1722, -1661, -318, +49), ICOS (+1720), CD28 (+17) and PD.1 (PD.1.3, PD.1.9) gene polymorphisms were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…To date, there is no clinical evidence that ICOS polymorphisms are associated with acute or chronic GVHD (37, 38), but larger studies covering the entire ICOS and ICOS-L locus in non-ethnical biased studies are warranted before any conclusions can be drawn. To our knowledge, only one study based on bioinformatics analysis found that low levels of ICOS mRNA were associated with acute GVHD (39), a result contrasting with our findings in the xeno-GVHD settings, showing massive upregulation of ICOS on transferred T cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no clinical evidence that ICOS polymorphisms are associated with acute or chronic GVHD (37, 38), but larger studies covering the entire ICOS and ICOS-L locus in non-ethnical biased studies are warranted before any conclusions can be drawn. To our knowledge, only one study based on bioinformatics analysis found that low levels of ICOS mRNA were associated with acute GVHD (39), a result contrasting with our findings in the xeno-GVHD settings, showing massive upregulation of ICOS on transferred T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of co-stimulatory pathways and attempts to use CTLA-4-Ig to prevent GvHD in animal models (Blazar et al 1996 ;Ichiki et al 2006 ), several published reports evaluated the association between donor CTLA-4 gene polymorphisms and outcome after hematopoietic stem cell transplantation (Bosch-Vizcaya et al 2012 ;Iravani-Saadi et al 2014 ;Mossallam and Samra 2013 ;Perez-Garcia et al 2009 ;Piccioli et al 2010 ). However, the results presented in these studies were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cells (HSCs) are precursors that have the ability to differentiate into all types of blood cells, including leukocytes, erythrocytes, and platelets, which are found in blood products [14]. In 2009, Li XC et al pointed out that costimulatory molecules play an important role in acute graft-versus-host disease (GVHD) [15] and it was found that polymorphism of costimulatory molecules, including CTLA4 and ICOS, might be associated with GVHD in allogeneic hematopoietic stem cell transplantation (HSCT) [16]. Moreover, both CTLA4 and ICOS gene polymorphisms in the donor and recipient might be of importance for the outcome of allogeneic HSCT [17].…”
Section: Introductionmentioning
confidence: 99%